Cutaneous filarioid nematodes of dogs in the United States: Are they emerging, neglected, or underdiagnosed parasites? - Gruntmeir, Jeff; Kelly, Maureen; Ramos, Rafael Antonio Nascimento; Verocai, Guilherme Gomes (Frontiers in Veterinary Science, 2023)
Filarioid nematodes of dogs are medically important, vector-borne parasites of cosmopolitan distribution. They are represented by species in which microfilariae are found circulating in the bloodstream (e.g., Dirofilaria sp., Acanthocheilonema sp. and Brugia sp.) or skin-dwelling (e.g., Cercopithifilaria sp. and Onchocerca sp.). Those species in which microfilariae are detected in blood have been extensively studied, especially Dirofilaria immitis, due to its clinical importance. In recent decades, there has been an increased interest by scientific community on filarioid nematodes in which microfilariae are detected in the skin, because of the zoonotic aspect of Onchocerca lupi. Although, in the United States (US), D. immitis has been considered the main filarioid infecting dogs, the intense animal movement and global canine filarioid diversity, may indicate that likely the presence of cutaneous filarioid nematodes is more common than we expected. Hence, a question remains: Are these canine filarioid nematodes emerging, neglected, or simply underdiagnosed in the US? In this review we provide an overview of pertinent information which briefly summarizes the biology of the different canine filarioid nematode species, clinical signs associated with infections, and currently available diagnostic tolls using molecular and microscopy-based methods, and highlight knowledge gaps where research and surveillance efforts remain necessary. Data herein presented serve as alert to the scientific community about the importance of filarioid nematodes infecting dogs, other than D. immitis. Additionally, the zoonotic potential of several filarioid species reinforces the necessity of a proper diagnosis and the need for broader surveillance in order to understand their diversity and distribution, introduction of certain species, and mitigate their establishment in the country, and new animal and human cases.